Intracellular Delivery of Therapeutic Protein via Ultrathin Layered Double Hydroxide Nanosheets - He Zhang; Anle Ge; Yulin Wang; Boran Xia; Xichu Wang; Zhonghui Zheng; Changsheng Wei; Bo Ma; Lin Zhu; Rose Amal; Sung Lai Jimmy Yun; Zi Gu (MDPI AG, 2024)
The therapeutic application of biofunctional proteins relies on their intracellular delivery, which is hindered by poor cellular uptake and transport from endosomes to cytoplasm. Herein, we constructed a two-dimensional (2D) ultrathin layered double hydroxide (LDH) nanosheet for the intracellular delivery of a cell-impermeable protein, gelonin, towards efficient and specific cancer treatment. The LDH nanosheet was synthesized via a facile method without using exfoliation agents and showed a high loading capacity of proteins (up to 182%). Using 2D and 3D 4T1 breast cancer cell models, LDH-gelonin demonstrated significantly higher cellular uptake efficiency, favorable endosome escape ability, and deep tumor penetration performance, leading to a higher anticancer efficiency, in comparison to free gelonin. This work provides a promising strategy and a generalized nanoplatform to efficiently deliver biofunctional proteins to unlock their therapeutic potential for cancer treatment.